Follicular Helper CD4+ T Cells in Human Neuroautoimmune Diseases and Their Animal Models - Xueli Fan; Chenhong Lin; Jinming Han; Xinmei Jiang; Jie Zhu; Tao Jin (Hindawi Limited, 2015)
Follicular helper CD4+ T (TFH) cells play a fundamental role in humoral immunity deriving from their ability to provide help for germinal center (GC) formation, B cell differentiation into plasma cells and memory cells, and antibody production in secondary lymphoid tissues. TFH cells can be identified by a combination of markers, including the chemokine receptor CXCR5, costimulatory molecules ICOS and PD-1, transcription repressor Bcl-6, and cytokine IL-21. It is difficult and impossible to get access to secondary lymphoid tissues in humans, so studies are usually performed with human peripheral blood samples as circulating counterparts of tissue TFH cells. A balance of TFH cell generation and function is critical for protective antibody response, whereas overactivation of TFH cells or overexpression of TFH-associated molecules may result in autoimmune diseases. Emerging data have shown that TFH cells and TFH-associated molecules may be involved in the pathogenesis of neuroautoimmune diseases including multiple sclerosis (MS), neuromyelitis optica (NMO)/neuromyelitis optica spectrum disorders (NMOSD), and myasthenia gravis (MG). This review summarizes the features of TFH cells, including their development, function, and roles as well as TFH-associated molecules in neuroautoimmune diseases and their animal models.